AB0597 Sjogrenser Cohort: Clinical and Epidemiological Features of Primary SjÖgren's Syndrome in Spanish Rheumathology Departments. (9th June 2015) - Fernandez Castro, M.; Andreu, J.L.; Martínez Taboada, V.; Olivé, A.; Rosas, J.; Sánchez-Piedra, C.; Menor, R.; Rodriguez, B.; García Aparicio, A.; Lόpez Longo, F.J.; Manrique-Arija, S.; García Vadillo, J.A.; et al.
Abstract : Background: Primary Sjögren syndrome (pSS) is a systemic autoimmune disease affecting primarily the exocrine glandular system that requires a multidisciplinary approach. Objectives: The aim of our study was to describe the clinical and epidemiological features of a pSS's cohort of patients visited in Spanish Reumathology Departments Methods: This is a multicenter descriptive transversal study of pSS patients fulfilling European/American consensus criteria from thirty three Rheumatology departments. Patients were included by randomisati from an anonymized list provided by every department. Data were collected by reviewing clinical records and an interviewing the patients. Informed consent was obtained and local ethics committees approved the study. Variables were analysed by descriptive statistical methods, using means, medians, and rates, with their deviations and interquartile ranges (p25-p75). Results: Four hundred and thirtyseven patients were included. Ninety five percent of them were women, with a median age of 58. Eighteen percent of the patients had a familiar history of autoimmune disease, most commonly rheumatoid arthritis. Median age at the time of the first symptoms was 46 years and at pSS's diagnosis was 50 years. Ocular symptoms (94%) were the most frequent complaint, followed by mouth dryness (94%), and ocular foreign body sensation (92%). Schirmer's test was performed in 402 patients and was positive in 85% of the cases. Basal salivary flow test was performed in 133 patients, and 89% were positive. Rose Bengal staining test was performed in 144 patients and was positive in 81 percent of them. Salivary gland scintigraphy was performed in more than fifty percent of patients and 87% showed abnormal results. Salivary gland biopsy was obtained in 193 patients, fulfilling histological criteria in 69% of them. Anti-Ro/SS-A, in 93% of the cases, and anti-La/SS-B, in 67%, were found positive during follow up. Only 27% of the patients fulfilled the new 2012 SICCA-ACR classification criteria. Conclusions: The clinical and demographical profile of pSS patients from Spanish rheumatology departments is similar to that previously described in other series. Diagnostic delay is substantial. A majority of patients showed ocular and oral symptoms. Schirmer test was the preferred diagnostic test used for dry eye evaluation. Only a small group of patients fulfilled the new 2012 ACR classification criteria. Disclosure of Interest: None declared